Just ask! : be different, be brave, be you - Sotomayor, Sonia, 1954- (New York : Philomel Books, 2019)
A story in which friends who have different abilities, work together to build a community garden.
Publishers Weekly, July 2019
2.9.
K-3.
Some copies purchased with funds from Altrusa International of Corvallis
Keywords: Individuality -- Juvenile fiction; Community gardens -- Juvenile fiction; Friendship -- Juvenile fiction; Individuality -- Fiction; Community gardens -- Juvenile fiction; Friendship -- Fiction